The Effect of Progestin Injection Contraception on Changes in Amount of Fat and Muscle in Female Patients at Slamet Riyadi Hospital, Surakarta - SUKAMTI, SRI; Prastyoningsih, Aris; Bumi Pangesti, Christiani (Journal of Advanced Nursing and Health Sciences, 2024)
This study aims to determine the effect of Progestin Injection Contraception on changes in the amount of fat and muscle in female patients at Slamet Riyadi Hospital, Surakarta. The research method used a quantitative research design with a Quasi-Experimental approach and a one-group pretest-posttest design. The population in this study was women who used progestin injection contraception as a method of contraception in the last three months, totaling 20 acceptors. Meanwhile, the sample of this study was 14 people. This research was conducted at Slamet Riyadi Hospital, Surakarta, over three months. Data analysis consisted of two stages: univariate analysis and bivariate analysis. The results showed that there was an effect of Progestin Injection Contraception administration on changes in fat and muscle levels before and after, with P values of 0.006 and 0.027, respectively. Therefore, these findings underscore the importance of monitoring body composition for Progestin Injection Contraception users and the need for further studies to understand the long-term impact of this type of contraception. muscle